MARKET JUSTICE FROM ISLAMIC BUSINESS ETHICS PERSPECTIVE - Rokan, Mustafa Kamal (Journal of Shariah Law Research, 2020)
In Indonesia, modern retail market has been entered into Indonesia since 1970. It’s been more expand 1998 by legal instrument which gives free to foreign investor to join this sector. Liberalization and monopolization of retail modern market have made the existence and rights of economics access of merchant traditional market marginalized, demolished even murdered. This paper want to introduce Islamic law transaction (fiqh mu‘āmalah) such as prohibition of iḥtikār (hoarding), ṭalāq rukban (entry barrier), ta‘alluq (collusive dealing) toward market justice for vulnerable society, in particular for the merchant of traditional market. This paper is using qualitative method research and case approach, especial decision of Business Competition Supervisory Commission (KPPU) No. 03/KPPU-LI/2000 and No. 9/KPPU-L/2009 on Islamic business ethics. This paper is proposing Islamic Business Ethic become Islamic Antimonopoly Law.